Rat somatic genome editing enables ER+ breast cancer modeling - Wen Bu; Tobie D. Lee; Meenakshi Anurag; Yongchao Dou; Yunfeng Ding; Zhiao Shi; Ruixin Xu; Lillian He; Alexandria Z. Bu; Chandandeep Nagi; Carolina Gutierrez; Jing Wang; et al. (Proceedings of the National Academy of Sciences, 2026)
Genetically engineered mouse models have advanced cancer research, but they fail to mimic some human diseases. Rats offer a powerful alternative for modeling human cancers that are inadequately represented in mice, yet their use has been constrained by technical barriers to genome editing. Here, we report somatic genome editing in rats and apply this approach to model estrogen receptor (ER)-positive breast cancer, which accounts for approximately 70% of human cases but remains poorly represented in mice. The resulting rat tumors reproduce hallmarks of human ER+ breast cancer, including ductal histology, hormone responsiveness, and immune microenvironment features. By contrast, identical genetic alterations in mice failed to yield ER+ tumors, underscoring critical species differences in tumorigenesis. Together, this work establishes a versatile platform for the rapid generation of clinically relevant rat tumor models, opening avenues to study tumor biology, therapeutic response, and immune interactions in cancer subtypes previously inaccessible to experimental modeling.